2019
DOI: 10.14686/buefad.490131
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Analysis of The Articles Published in The Last 10 Years Within The Context of Lifelong Learning

Abstract: The purpose of this study is to analyze in a descriptive way the published work within the context of lifelong learning in the last decade. For this purpose, the SCI-Expanded, SSCI and A&HCI citation indexes in the Web of Science were used. The following search terms were used as appropriate: "Lifelong Learning" and "Lifelong Learning". A total of 297 articles were found in the search results and these studies were analyzed according to the journal they published, the language, the research methods and their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…In this sense, it is of primary importance to determine the factors affecting lifelong learning tendencies of students in faculty of education, regarded as future prospective teachers. In line with this, several scholars have focused on teachers' and prospective teachers' lifelong learning skills (Cetin & Cetin, 2017;Cropley & Dave, 2014;Day, 2002;Deveci & Ayish, 2017;Gencel, 2013;Ilgaz & Eskici, 2018;Kılıç & Yılmaz, 2019;Kılıç, 2014;Yıldız-Durak & Şahin, 2018). On the other hand, a systemic review of literature has revealed that there is a gap in terms of research on the relation between lifelong tendencies and such variables as demographic information, ICT usage status, the number of trainings for personal and professional development, self-directed learning and thinking styles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, it is of primary importance to determine the factors affecting lifelong learning tendencies of students in faculty of education, regarded as future prospective teachers. In line with this, several scholars have focused on teachers' and prospective teachers' lifelong learning skills (Cetin & Cetin, 2017;Cropley & Dave, 2014;Day, 2002;Deveci & Ayish, 2017;Gencel, 2013;Ilgaz & Eskici, 2018;Kılıç & Yılmaz, 2019;Kılıç, 2014;Yıldız-Durak & Şahin, 2018). On the other hand, a systemic review of literature has revealed that there is a gap in terms of research on the relation between lifelong tendencies and such variables as demographic information, ICT usage status, the number of trainings for personal and professional development, self-directed learning and thinking styles.…”
Section: Discussionmentioning
confidence: 99%
“…Dinevski ve Dinevski (2004) ise yaşam boyu öğrenmeyi, okul sınırları dışında diğer bir deyişle informal eğitim süreci içerisinde meydana gelen öğrenmeler olarak tanımlamıştır. Günümüzde toplumsal yaşamın yapısında meydana gelen değişiklikler ve mesleki ya da kişisel çeşitli yeterliklerle ilgili süreklilik arz eden değişimler (Kılıç & Yılmaz, 2019) gibi gelişmelere ayak uydurabilmek için bireyler yeni bilgiler öğrenme ihtiyacı duymakta ve sürekli olarak öğrenme süreci içerisine kalmaktadır. Öğrenme süreci, okul sınırları içerisinde meydana gelen formal eğitim ile sınırlı kalmayıp okul sınırları dışında gerçekleşen informal eğitim sürecini de kapsamaktadır (Ayaz, 2016).…”
Section: öğRetmen Adaylarının Yaşam Boyu öğRenme Eğilimleri: Yordayıcı Olarak öZ Yönetimli öğRenme Düşünme Stilleri Bi̇t Kullanım Durumu unclassified
See 1 more Smart Citation
“…Therefore, it is important to find out the pre-service teachers' views towards lifelong learning. Thematic studies on the concept of lifelong learning have been undertaken since 2009 (Yenen et al, 2016;Yüksel et al, 2016;Kılıç, & Yılmaz, 2019;Kılınç & Uzun, 2020). Many of these studies consisted of research studies in different fields and samples.…”
Section: Introductionmentioning
confidence: 99%